STUDYING OF THERMAL ANNEALING EFFECT ON STRUCTURALAND OPTICAL PROPERTIES OF CU2O THIN FILMS PREPARED BYPLASMA SPUTTERING METHOD - Sangery, A.; Sebber, A.; Dawood, A.; Abbas, S.; Khalaf, H. (Iraqi Journal of Science, 2024)
In this study we prepare Cu2O films by using plasma sputtering method onsubstrate from glass type Pyrex; we used system of dipole sputtering with magneticfield. We studied the optical and structural properties to Cu2O and we studiedthermal annealing with 150◦C on optical and structural properties for prepared thinfilms with thickness 2000Ǻ for one hour. It showed that the thermal annealing leadsto increase of optical energy gap. We used x-rays diffraction for diagnostic structureand nature thin film material. the results appear that the thin film is poly crystallinestructure, the thermal annealing leads to drop of diffraction peaks and increase itedges that's means it become more uniformity as well as it consist of opticalproperties study about spectrum record for absorbance and transmission for theprepared thin films in visible region and ultraviolet for range of wave length 300-900 nm.